Effect of Electroacupuncture on Reproductive Disorders and Insulin Resistance in a Murine Polycystic Ovary Syndrome Model. (26th December 2021) - Ji, Chang; Xu, Wanling; Zhang, Zhiqing; Cui, Shuai; Yi, Wei
Abstract : Polycystic ovarian syndrome (PCOS) is a common, complex, and heterogeneous endocrine and metabolic disorder. There is no standardized treatment, and it therefore requires individualized therapies according to the symptoms and pathogenesis of each patient. The present study aimed to determine the effect of electroacupuncture at the acupoints Zusanli (ST36), Sanyinjiao (SP6), and Neiguan (PC6) on reproductive disorders and insulin resistance in a murine model of PCOS induced by dehydroepiandrosterone (DHEA). Vaginal smear analysis was used to determine mice estrous cycle; intraperitoneal glucose and insulin tolerance tests were adopted to analyze metabolic characteristics; enzyme-linked immunosorbent assay was used to measure hormone levels; gene expression was quantified with real-time PCR; hematoxylin and eosin staining was used to observe ovarian morphology. We observed disordered estrous cycle, polycystic ovarian morphology, and higher levels of homeostasis model assessment-insulin resistance (HOMA-IR) and testosterone (T), indicating successful modeling of PCOS. DHEA increased levels of estrogen (E2 ), progesterone (P), testosterone (T), luteinizing hormone (LH), and follicle-stimulating hormone (FSH), and EA treatment restored them to levels seen in the control group. EA reduced the days in estrus caused by DHEA, improved the abnormal sex hormone receptor genes, and attenuated the DHEA-induced histomorphological changes in mouse ovaries. The average expressions of the androgen receptor (AR), estrogen receptor (ER), luteinizing hormone receptor (LHR), and follicle-stimulating hormone receptor (FSHR) genes in the ovary greatly increased after DHEA treatment and significantly decreased in the DHEA + EA group. After EA treatment, the cystic follicle (CF) number was reduced and corpora lutea (CL) increased in the DHEA + EA group compared to the DHEA group. EA improved glucose intolerance and insulin intolerance. Statistical analysis of intraperitoneal glucose tolerance test-area under curve (IPGTT-AUC) glucose levels revealed a significant decrease in DHEA group mice compared to the control and DHEA + EA groups. EA was found to restore fasting blood glucose, fasting serum insulin, and HOMA-IR. In summary, our study suggests that EA has a remarkable effect in the DHEA-induced murine PCOS model. Management of EA could improve estrous cycle, hormonal disorders, abnormal sex hormone receptors in ovaries, ovary morphology, and insulin resistance in PCOS mice.